2007
DOI: 10.1002/pbc.20623
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of infantile choriocarcinoma of the liver

Abstract: Primary choriocarcinoma of the liver is an extremely rare childhood malignancy frequently associated with clinical instability at initial presentation. It often mimics other benign and malignant childhood liver tumors. Prompt diagnosis and initiation of treatment are necessary to attain a successful outcome. We describe a critically ill infant with metastatic choriocarcinoma whose diagnosis was based on radiographic and tumor marker findings, without an initial biopsy, and her successful management with neo-ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 15 publications
1
14
0
1
Order By: Relevance
“…In the literature, there are less than 30 cases of primary hepatic germ cell tumors reported including yolk sac tumor [26][27][28], mixed germ cell tumors [6,29], and choriocarcinomas [3,4,24]. Among the primary choriocarcinomas of the liver, the vast majority of them were of infantile type (some of which may represent metastases from occult placental choriocarcinoma) [24,30]. In previous studies, only two well-documented adult cases have been reported [3,4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, there are less than 30 cases of primary hepatic germ cell tumors reported including yolk sac tumor [26][27][28], mixed germ cell tumors [6,29], and choriocarcinomas [3,4,24]. Among the primary choriocarcinomas of the liver, the vast majority of them were of infantile type (some of which may represent metastases from occult placental choriocarcinoma) [24,30]. In previous studies, only two well-documented adult cases have been reported [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…In spite of these strict criteria, there are indeed still some extragonadal (other than uterine, testes, and ovary) choriocarcinomas . Most reported primary extragonadal choriocarcinomas were in the mediastinum [1,7,8,14,16,20,21] and stomach [13], and only very rarely such choriocarcinomas occur in liver [3][4][5]24]. Most reported primary hepatic choriocarcinomas were of infantile type (their origin was still controversial, and they may represent metastasis from occult placental choriocarcinoma) [5,24], and there were only two welldocumented cases in adults [3,4].…”
Section: Introductionmentioning
confidence: 98%
“…Choriocarcinoma usually has heterogeneous T1 and T2 signal intensity with large areas of central necrosis. T1 hyper-intense hemorrhagic areas are frequently encountered in addition to fluid filled cysts with high protein content that are T1 and T2 hyper-intense and these features are like ovarian choriocarcinoma [12,16]. When compared to uterine choriocarcinoma, the imaging features are similar except that uterine choriocarcinoma tend to be infiltrative rather than presenting with masses.…”
Section: Discussionmentioning
confidence: 99%
“…β-hCG levels can be followed throughout the treatment to assess the response to chemotherapy, and to detect recurrences in both mother and child. These tumors are highly vascular and friable, so biopsy may be difficult and even dangerous (Yoon et al, 2007). As such, in the infant we describe, treatment begun immediately without tumor biopsy.…”
Section: Commentmentioning
confidence: 91%
“…Therefore, early interventionwhich can be difficult because of the rarity of the disease -is critical for limiting the progression of disease. In infants, without appropriate treatment, death usually occurs within 3 weeks of initial presentation (Yoon et al, 2007). Fortunately, despite its aggressive nature, this cancer responds very well to chemotherapeutic agents, even in the presence of widespread metastases.…”
Section: Commentmentioning
confidence: 97%